(untitled) (Journal of Nobel Medical College, 2018)
Background: Scoliosis is common in children of school going age particularly in the adolescents. This condition is asymptomatic and often children present in the advanced stage of this condition with large deformity. Therefore, early detection avoids the problems associated with large curves. Material and Methods: Retrospective analysis of data obtained from screening of eight schools in the eastern part of Nepal between April 2016 and May 2017 was done; Morang district (5 schools) and Sunsari district (3 schools). A consultant Orthopaedic Surgeon, a trained Physiotherapist and an Orthopaedic nurse conducted school screening for scoliosis using the Adam’s forward bend test in the Morang district while the latter two were involved in screening in the Sunsari district. The data collected included demographics, number of positive cases and treatment prescribed. Results: 5505 children 2840 boys (51.6%) and 2665 girls (48.4%) were screened for scoliosis in this period. Majority of patients were from the Morang district (86.2%). All six children (five girls and one boy) who were found to have positive Adam’s forward test had adolescent idiopathic scoliosis. One child had a curve of 35 degrees and bracing was started. Rest of the children had curves less than 25 degrees and were kept on regular follow up. The referral rate was 1.1 per 1000 children screened for scoliosis. Conclusion: Though the overall prevalence of scoliosis appears to be less in our population, school screening is still important for two main reasons. This may be the only way to detect cases early so that treatment can be instituted before deformity becomes large. Secondly, this activity would also spread awareness about this little known condition in the community. Journal of Nobel Medical College Volume 7, Number 1, Issue 12, January-June 2018, Page: 37-40